Retos del acceso al agua y su saneamiento desde el enfoque de derechos humanos en zonas urbanas desfavorecidas de Tuxtla Gutiérrez, Chiapas = Challenges of access to clean water and its sanitation from the human rights approach in deprived urban areas of Tuxtla Gutiérrez, Chiapas - Escobar, Mayra Isuí Cruz (Oñati Socio-Legal Series, 2024)
The theoretical debates about the nature of water and its relationship with urban inequalities are analyzed to accentuate the importance of water as a social and cultural good, recognizing that people have right to Access to clean water in deprived urban, as is the case of north-west area of Tuxtla Gutiérrez, Chiapas where there are inequalities in its access, health and sanitation. This article was carried out using a qualitative methodology, consulting primary and secondary sources. The objective was to contribute to the socio-legal analysis of the human right to clean water and sanitation from rights based approach, examining human rights principles such as equality, non-discrimination and participation as criteria that guide public policy decisions to contribute to the effective enjoyment of human rights. It is concluded that there must be a base of regulatory criteria for water and its sanitation that focus on addressing water as a social and cultural good and as a right to combat urban inequalities.